Language complexity trade-offs revisited - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2020)
In this paper we revisit the results that originally appeared in Coloma (2015) and Coloma (2017), using a newly-assembled database of 50 languages for which we have the same text (which is the fable known as "The North Wind and the Sun"). Most conclusions of the original papers remain the same, especially the ones that signal the existence of language complexity trade-offs. This is particularly clear when we look at partial correlation coefficients between three linguistic ratios (phonemes per syllable, syllables per word, and words per clause), when we use simultaneous-equation regression methods, and when we estimate different versions of Menzerath law that relate phonemes per word and words per clause.
Keywords: 330; complexity trade-off; partial correlation; linguistic ratios; simultaneous-equation regression; Menzerath law; The North Wind and the Sun